Economic policy and state intervention : selected papers of T.N. Srinivasan - Srinivasan, T. N., 1933-; Narayana, N. S. S. (New Delhi ; New York : Oxford University Press, 2001)
With reference to developing countries.
Includes bibliographical references.
Keywords: India -- Economic policy -- 1991-; India -- Economic conditions -- 1947-; India -- Politics and government -- 1977-